How Commissives Depend on Representatives: An Illocutionary Analysis of Collective Identity in Zohran Mamdani’s Election Victory Speech - Dian Marisha Putri; Sari Gracya Laura Sianturi; Salwa Salsabillah; Amila Nirina Nasution; Maysa Lani (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
Political victory speeches are strategic discursive tools used to build public legitimacy and construct political identity. This article investigates the linguistic strategies in Zohran Mamdani’s 2025 mayoral victory speech, focusing on the interplay between representative and commissive speech acts through John Searle’s pragmatic framework. Employing a descriptive qualitative method, this study analyzes how the speaker constructs collective agency and aligns political commitments with the United Nations Sustainable Development Goals (SDGs). The findings demonstrate that Mamdani utilizes representative acts as preparatory conditions to vest political ownership in the collective, which subsequently transforms commissive acts into collectivized commitments. Furthermore, the analysis reveals a significant alignment between these policies and SDG targets 11.1, 11.2, 3.8, and 16.5, suggesting that the speech performatively enacts the participatory governance prescribed by SDG 16.7. This research contributes to the study of political pragmatics by highlighting the constitutive relationship between speech acts, providing a framework for analyzing how discourse actively constructs the collective agency necessary for democratic governance. Keywords: Sustainable Development Goals, Speech act theory, Illocutionary Act